Network Meta-analysis of efficacy of integrated traditional Chinese and western medicine for acute kidney injury - Luo Pu-chang; Chen Hong-bo (Linchuang shenzangbing zazhi)
ObjectiveTo compare the therapeutic efficacy of western medicine versus different traditional Chinese medicines （TCM） for acute kidney injury （AKI） patients.MethodsLiterature items were retrieved from the databases of CNKI， Wanfang and Sinomed. And R software was employed for network Meta-analysis on the final included literatures.ResultsA total of 32 literature items were included. The traditional Chinese medicines involved oral TCM， TCM injection and TCM enema. The network Meta-analysis showed that the total effective rate of western medicine treatment plus oral TCM preparation and TCM enema was the best； in terms of lowering serum creatinine， western medicine treatment plus oral TCM and TCM enema are the best； in terms of reducing blood urea nitrogen， western medicine treatment plus oral TCM was the best.ConclusionCombined use of western medicine and various TCM treatments can boost the overall effective rate and improve related parameters.